APPLICATION OF LEED ENVIRONMENTAL CERTIFICATION CRITERIA IN A POPULAR MARKET HOUSING (REMUNOM, 2024)
Since the intensification of the climate changes on a global scale, the architecture can contribute to the downsize of the environmental impacts from more sustainable constructions. In that regard, this article intends to study the application of the environmental certification Leadership in Energy and Environmental Design (LEED) - which consists in a certification aimed at sustainable constructions, designed and granted by a North American organization - standards in a Popular Market Housing project, elaborated by the author herself, in the city of Belém in Pará. In methodological terms, this was a bibliographic research, in which were considered books, book chapters, sites of governmental organs and qualified scientific papers. Throughout the development of the project, many techniques based on the sustainability of the constructions were considered, the main one being Low Impact Development. From the perspective of project evaluation, the list offered by the LEED certification was used, besides two softwares, the Flow Design and the Velux Daylight. The first one evaluates the airing by simulating a virtual wind tunnel to visualize the air flow inside and around the building. The second one, was used to certify the performance regarding access to natural lighting. Moreover, through the standard checklist, it is considered that the design proposal is capable of attending the mandatory and non mandatory requirements and to achieve 63 points, including the requirement of producing renewable energy and optimizing the energy consumption of the home. Therefore, such strategies, yet barely used in Brazil, can bring benefits both environmentally, aiming to reduce the use of natural resources and generation of pollutants, as possible financial savings and improve quality of life to the user population of the sustainable architecture.